+0  
 
0
319
2
avatar

I'm kind of stuck on this one: My answer is -b^2 + 1 / 4b^2 - 7b + 3

Guest Mar 18, 2015

Best Answer 

 #1
avatar+17745 
+5

The common denominator for all the denominators is b(b - 1).

Multiply both the numerator and the denominator by this expression.

Numerator: [ (1/b - 2/(b - 1) ] x (b)(b - 1)  =  1(b - 1) - 2(b)  =  b - 1 - 2b  =  -1 - b

Denominator:  [ 3/b + 1/(b - 1) ] x (b)(b - 1)  =  3(b - 1) + 1(b)  =  3b - 3 + b  =  4b - 3

Answer:  (-1 - b) / (4b - 3) 

geno3141  Mar 18, 2015
 #1
avatar+17745 
+5
Best Answer

The common denominator for all the denominators is b(b - 1).

Multiply both the numerator and the denominator by this expression.

Numerator: [ (1/b - 2/(b - 1) ] x (b)(b - 1)  =  1(b - 1) - 2(b)  =  b - 1 - 2b  =  -1 - b

Denominator:  [ 3/b + 1/(b - 1) ] x (b)(b - 1)  =  3(b - 1) + 1(b)  =  3b - 3 + b  =  4b - 3

Answer:  (-1 - b) / (4b - 3) 

geno3141  Mar 18, 2015
 #2
avatar
0

Thank you Geno!

Guest Mar 19, 2015

30 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.